2004
DOI: 10.7863/jum.2004.23.6.769
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of Urethral Anomalies in Infants

Abstract: Our data show that sonography of the urethra is a valuable tool for diagnosis of urethral anomalies. Especially, negative findings on sonography are highly suggestive of the absence of urethral anomalies. Positive or equivocal sonographic findings should indicate VCUG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[ 1 ] It is commonly associated with PUV as seen in this case. [ 5 8 ] In the majority of cases, it occurs as a result of a primary maturation abnormality of the vesicoureteral junction or a short distal ureteric submucosal tunnel in the bladder that alters the function of the valve mechanism. [ 6 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] It is commonly associated with PUV as seen in this case. [ 5 8 ] In the majority of cases, it occurs as a result of a primary maturation abnormality of the vesicoureteral junction or a short distal ureteric submucosal tunnel in the bladder that alters the function of the valve mechanism. [ 6 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 3 4 ] Vesicoureteral reflux (VUR) is commonly associated with PUV[ 5 6 ] and is present in 50% of cases. [ 7 8 ] Patent urachus frequently coexists with congenital lower urinary tract obstruction and it is associated with PUVs in about one-third of cases. [ 9 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…To avoid these semi-invasive procedures, ultrasound can be of additional help to differentiate between the above-mentioned three most common entities, each requiring a totally different approach [8]. We have used a high frequency linear array transducer (12-5 MHz) and applied the panoramic approach to enlarge the region of interest in order to evaluate more clearly the relation of the mass with the surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the radiology database on the sonographic diagnosis of urethral anomalies in infants, Helmut Schoellnast et al found that the overall sensitivity of urethral sonography for detection of urethral anomalies was 100%; specificity, 94%; positive predictive value, 58%; negative predictive value, 100%; and accuracy, 94% [8].…”
Section: Discussionmentioning
confidence: 99%